The THE IMPLICATION OF JOB SATISFACTION THAT INFLUENCE WORKERS TO PRACTICE ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN THE WORK PLACE - Soelton, Mochamad (Archives of Business Research, 2020)
This research aims to examine and analyze the political organization, organizational climate and organizational culture with organizational citizenship behavior (OCB) and job satisfaction as an intervening variable for employees of Distributor Company. The object of this research is 73 employees of Distributor Company. The approach used in this research is Component or Variance Based Structural Equation Model with analysis tool Smart-PLS. The results showed Political organizationa that has positive significant effect on job satisfaction. Organizational climate that has positive significant effect on job satisfaction to employees Distributor Company. Organizational culture that has positive significant effect on job satisfaction. Political organization does not affect organizational citizenship behavior (OCB). Organizational climate that has positive significant effect on organizational citizenship behavior (OCB). Organizationa culture that has positive significant effect on organizational citizenship behavior (OCB). Job satisfaction that has positive significant effect on organizational citizenship behavior (OCB).